2016 6th International Conference on Information Communication and Management (ICICM) 2016
DOI: 10.1109/infocoman.2016.7784260
|View full text |Cite
|
Sign up to set email alerts
|

Process mining in oncology: A literature review

Abstract: Abstract-Process mining, an emerging data analytics method, has been used effectively in various healthcare contexts including oncology, the study of cancer. Cancer is a complex disease with many complicated care requirements and there is an urgent need to improve the cost and clinical effectiveness of cancer care pathways. Process mining of the e-health records of cancer patients may play an important future role and this paper presents a literature review of process mining in oncology as a contribution to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 49 publications
(100 reference statements)
0
37
0
Order By: Relevance
“…Our review of the process mining literature identified 37 peer reviewed papers using electronic health record (EHR) data to map pathways in oncology (11). Challenges included the difficulty of capturing outpatient events (12), the use of data collected for non-clinical purposes, missing data and clinically inaccurate time-stamps (13).…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the process mining literature identified 37 peer reviewed papers using electronic health record (EHR) data to map pathways in oncology (11). Challenges included the difficulty of capturing outpatient events (12), the use of data collected for non-clinical purposes, missing data and clinically inaccurate time-stamps (13).…”
Section: Introductionmentioning
confidence: 99%
“…Of the 27 review papers in Table A2 (Appendix II), six consider process mining or data mining [38,63,78,109,135,168], seven consider simulation [2,105,132,173,175,176,208] and three consider stochastic modelling [59,123,213].…”
Section: Previous Researchmentioning
confidence: 99%
“…There are seven papers that use the term 'clinical pathway', or its synonyms, in the search terms [61,63,132,156,173,175,189] and two papers use 'patient flow' in their search terms [109,173]. These papers all consider clinical pathways, but most focus on a different primary topic.…”
Section: Previous Researchmentioning
confidence: 99%
“…Our case study examined process data related to the treatment of endometrial cancer over a 15 year period (2003-2017) in one of the UK's largest cancer centres (Leeds Cancer Centre) with a specific focus on the routes to diagnosis. Process mining has been used and shown promising results to support process analytics in Oncology [8]. Our event logs were drawn from the Electronic Healthcare Record (EHR) system of Leeds Teaching Hospital NHS Trust.…”
Section: Introductionmentioning
confidence: 99%